Marketing Strategy Analysis Jambu Mete Using Analytical Hierarchy Procces (AHP) Approach (Case Study: UD. Azwan In Matano Oe Village Tongkuno District, Muna District) - Muhamad Safar; Sarinah Sarinah; Muhammad Syukri (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2021)
This study aims to determine the objectives of UD's cashew marketing strategy. Azwan uses the AHP method. Determination of stakeholders from the marketing strategy using the AHP method and to determine the alternative of the marketing strategy in the cashew business using the AHP method. Data was collected using the following methods: (a) interviews, (b) questionnaire/questionnaire techniques, and (c) documentation. The results showed that the cashew marketing strategy of the importance of each goal was an increase in income with a weighted value of (0.488), an increase in demand with a weighted value of (0.292); an increase in product quality with a weighted value of (0.118), and a price increase. Competing with a weighted value of (0.102). The selection of the stakeholder with the highest weight as a reference recommendation that underlies the selection of the cashew marketing strategy of the importance of each stakeholder, namely farmers with a weight value of (0.360), the government with a weight value of (0.145), companies with a weighting value of (0.255), academics with a weighted value of (0.112), and finance with a value of (0.129). The assessment of alternative strategies resulted in the highest weighting successively for the design of increasing and utilizing existing resources with a weighted value of (0.223), product development strategies with a weighted value of (0.357), and the need for market share strategies with a weighting of (0.311).